It's a wonderful life. - Stewart, James, 1908-; Reed, Donna, 1921-1986.; Travers, Henry; Capra, Frank, 1897- (New York : RKO Radio Pictures, 1946)
A would be suicide is saved by an elderly angel who points out how his small town friends would have missed him had he not lived.
Tape copy.
Produced and directed by Frank Capra.
James Stewart, Donna Reed and Henry Travers.
Keywords: Feature films